Functional connectivity in a monetary and social incentive delay task in medicated patients with schizophrenia - Hanewald, Bernd; Lockhofen, Denise Elfriede Liesa; Sammer, Gebhard; Stingl, Markus; Gallhofer, Bernd; Mulert, Christoph; Iffland, Jona Ruben (Frontiers in Psychiatry, 2023)
Introduction Numerous studies indicate impaired reward-related learning in individuals with schizophrenia, with various factors such as illness duration, medication, disease severity, and level of analysis (behavioural or neurophysiological data) potentially confounding the results. Patients with schizophrenia who are treated with second-generation antipsychotics have been found to have a less affected reward system. However, this finding does not explain the neural dysfunctions observed in previous studies. This study aims to address the open question of whether the less impaired reward-related behaviour is associated with unimpaired task-related functional connectivity or altered task-related functional connectivity. Methods The study included 23 participants diagnosed within the schizophrenia spectrum and 23 control participants matched in terms of age, sex, and education. Participants underwent MRI while performing a monetary and a social incentive delay task. The collected data was analyzed in terms of behaviour and functional connectivity. Results Both groups exhibited a main effect of reward type on behavioural performance, indicating faster reaction times in the social incentive delay task, but no main effect of reward level. Altered functional connectivity was observed in predictable brain regions within the patient group, depending on the chosen paradigm, but not when compared to healthy individuals. Discussion In addition to expected slower response times, patients with schizophrenia demonstrated similar response patterns to control participants at the behavioural level. The similarities in behavioural data may underlie different connectivity patterns. Our findings suggest that perturbations in reward processing do not necessarily imply disturbances in underlying connectivities. Consequently, we were able to demonstrate that patients with schizophrenia are indeed capable of exhibiting goal-directed, reward-responsive behaviour, although there are differences depending on the type of reward.